Jimmy Robert - the man who envied women - Bell, Kirsty 1971-; İlk, Çağla ca. 20. Jh; Heide, Bart van der 1974-; Lebovici, Élisabeth 1953-; Meunier, Karolin 1975-; Rosengarten, Magnus Elias; Yıldız, Milas Adnan (Bierke Verlag, 2024)
Robert's first substantial overview covering 20 years of work including his most recent exhibitions at Palais de Tokyo, Moderna Museet, Museion, Crac Sète, Nottingham Contemporary and Kunsthalle Baden-Baden. It will include essays by Kirsty Bell, Elisabeth Lebovici, Bart van der Heide, Karolin Meunier and Çağla Ilk & Misal Adnan Yıldız. Given that Robert's practice is profoundly engaged with im/materiality, paper, texture and performance, the book will correspond with this approach through formal elements, surfaces and papers. Robert will also use it as a platform to crystalize his conceptual and dense, as well as open and processual steps in his work into another medium. The publication will further extend the site specifity and spatiality of his exhibitions and re-consider how a body can be perceived in other environments
Erratum: On pages 36, 37, and 40 the Arabic quote is incorrectly printed from left to right, it should be printed from right to left
Keywords: Robert, Jimmy -- 1975-; Paperback / softback; Kunst; Performance; Papier; 1580: Hardcover, Softcover / Kunst